2013
DOI: 10.1155/2013/109505
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Resection of Prostate Abscess: Is It Different from Conventional Transurethral Resection for Benign Prostatic Hyperplasia?

Abstract: Purpose. To present our experience of prostate abscess management by modified transurethral resection (TUR) technique. Methods. Seventeen men with prostate abscess undergoing TUR between 2003 and 2011 were retrospectively analyzed. Details of demography, surgical procedures, complications, and followup were noted. Results. With a mean age of 61.53 ± 8.58 years, all patients had multifocal abscess cavities. Initially, 6 men underwent classical TUR similar to the technique used for benign prostatic enlargement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…These patients, who are frequently older with coincident outlet obstruction, are at risk for PA from direct introduction of bacteria into the prostate. Along with multiple case reports, previous cross‐sectional studies have shown that 8–11% of patients presenting with PA had recently undergone prostate biopsies . In two such cases, PA was the result of infection with multidrug‐resistant Escherichia coli .…”
Section: Etiology and Natural Historymentioning
confidence: 91%
See 1 more Smart Citation
“…These patients, who are frequently older with coincident outlet obstruction, are at risk for PA from direct introduction of bacteria into the prostate. Along with multiple case reports, previous cross‐sectional studies have shown that 8–11% of patients presenting with PA had recently undergone prostate biopsies . In two such cases, PA was the result of infection with multidrug‐resistant Escherichia coli .…”
Section: Etiology and Natural Historymentioning
confidence: 91%
“…Along with multiple case reports, [21][22][23][24] previous cross-sectional studies have shown that 8-11% of patients presenting with PA had recently undergone prostate biopsies. 25,26 In two such cases, PA was the result of infection with multidrug-resistant Escherichia coli. 21,23 As patients undergoing transrectal prostate biopsy are frequently given antimicrobial prophylaxis, it is important to be mindful of the rising emergence of multidrug resistance in post-prostate biopsy infections.…”
Section: Etiology and Natural Historymentioning
confidence: 99%
“…19 The management options include transrectal ultrasonography-guided aspiration, transurethral incision over the abscess, transurethral deroofing of the abscess cavity, or formal transurethral resection of prostate. 20 No management algorithms are currently available to guide physicians in the surgical drainage, and the decision is usually based on physician preference.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Unlike holmium laser enucleation of the prostate (HoLEP), transurethral holmium laser deroofing of a prostatic abscess requires no further incision or resection between 10 o'clock and 2 o'clock, because the prostatic abscess is usually not located in the anterior zone of the fibromuscular stroma [ 6 ]. During this procedure, HoLEP was performed in patients with any residual obstructive adenoma [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the surgical interventions, such as open perineal drainage, transrectal ultrasound (TRUS)-guided needle aspiration, and transurethral resection of the prostatic abscess, transurethral drainage of the prostatic abscess is often performed in patients diagnosed with multiloculated abscesses, recurrent or residual abscesses, and associated bladder outlet obstruction [ 5 ]. Although many reports have focused on managing prostatic abscesses by use of conventional transurethral drainage, the use of a holmium laser to perform the transurethral approach has not yet been reported [ 4 , 5 , 6 ]. In this study, we describe the technical details of using a transurethral holmium laser for deroofing prostatic abscesses and we evaluate the effect of that procedure.…”
Section: Introductionmentioning
confidence: 99%